Effects of wearing a full body compression garment during recovery from an ultra-trail race. Issue 6 (3rd June 2021) - Martínez-Navarro, Ignacio; Aparicio, Inma; Priego-Quesada, Jose Ignacio; Pérez-Soriano, Pedro; Collado, Eladio; Hernando, Barbara; Hernando, Carlos
Abstract: In sport disciplines with high levels of muscle damage such as an ultra-trail competition, full body compression garments (FBCG) may have an ergogenic effect during the recovery process. The aim of the study was to assess the influence of FBCG worn for 24 h immediately after a 107-km ultra-trail on delayed onset muscle soreness (DOMS), muscle damage, inflammatory and renal response. Thirty-two athletes (19 males and 13 females; VO2peak : 54.1 ± 5.2 ml O2/kg/min) participated in the study. The following blood markers were analysed before, immediately after, at 24 and 48 h post-race: lactate dehydrogenase, creatine kinase, C-reactive protein and creatinine. The glomerular filtration rate was also calculated. Delayed onset muscle soreness was evaluated before, immediately after and at 24 h post-race. On arrival at the finishing line, athletes were randomised into one of two recovery groups (FBCG and control group). The results showed that wearing FBCG did not influence the evolution of any of the blood markers up to 48 h after the race ( p  > .05). However, FBCG group presented a lower increase in posterior leg DOMS (11.0 ± 46.2% vs 112.3 ± 170.4%, p  =   .03, d  =   0.8). Therefore, although FBCG is not useful for reducing muscle damage and inflammatory response after an ultra-trail race, its use may still be recommended as a recovery method to reduce muscle soreness. Trial registration: ClinicalTrials.gov identifier: NCT03990259.